Early Brassica Crops Responses to Salinity Stress: A Comparative Analysis Between Chinese Cabbage, White Cabbage, and Kale - Pavlović, Iva; Mlinarić, Selma; Tarkowská, Danuše; Oklestkova, Jana; Novák, Ondřej; Lepeduš, Hrvoje; Bok, Valerija Vujčić; Brkanac, Sandra Radić; Strnad, Miroslav; Salopek-Sondi, Branka (Frontiers in Plant Science, 2019)
Soil salinity is severely affecting crop productivity in many countries, particularly in the Mediterranean area. To evaluate early plant responses to increased salinity and characterize tolerance markers, three important Brassica crops - Chinese cabbage (Brassica rapa ssp. pekinensis), white cabbage (B. oleracea var. capitata) and kale (B. oleracea var. acephala) were subjected to short-term (24 h) salt stress by exposing them to NaCl at concentrations of 50, 100 or 200 mM. Physiological (root growth, photosynthetic performance parameters, and Na+/K+ ratio) and biochemical parameters (proline content, and lipid peroxidation as indicated by malondialdehyde, MDA, levels) in the plants' roots and leaves were then measured. Photosynthetic parameters such as the total performance index PItotal (describing the overall efficiency of PSI, PSII and the intersystem electron transport chain) appeared to be the most salinity-sensitive parameter and informative stress marker. This parameter was decreased more strongly in Chinese cabbage than in white cabbage and kale. It indicated that salinity reduced the capacity of the photosynthetic system for efficient energy conversion, particularly in Chinese cabbage. In parallel with the photosynthetic impairments, the Na+/K+ ratio was highest in Chinese cabbage leaves and lowest in kale leaves while kale root is able to keep high Na+/K+ ratio without a significant increase in MDA. Thus Na+/ K+ ratio, high in root and low in leaves accompanying with low MDA level is an informative marker of salinity tolerance. The crops' tolerance was positively correlated with levels of the stress hormone abscisic acid (ABA) and negatively correlated with levels of jasmonic acid (JA) and jasmonoyl-L-isoleucine (JA-Ile). Furthermore, salinity induced contrasting changes in levels of the growth-promoting hormones brassinosteroids (BRs). The crop’s tolerance was positively correlated with levels of BR precursor typhasterol while negatively with the active BR brassinolide. Principal Component Analysis revealed correlations in observed changes in phytohormones, biochemical and physiological parameters. Overall, the results show that kale is the most tolerant of the three species and Chinese cabbage the most sensitive to salt stress, and provide holistic indications of the spectrum of tolerance mechanisms involved.